Conﬂicting conventions: space as a medium in the works of Gerhard Richter and Serge Nitegeka - Wepener, Daneille (My University, 2017)
This dissertation aims to examine Gerhard Richter and Serge Nitegeka’s artistic practices, in order to understand and identify how artists can potentially use space as a medium and contextualise my own practice within this realm. I position the conventions and principles of space through reference to French theorists’ Henri Lefebvre, Michel de Certeau and Michel Foucault. The thesis begins with a brief overview of the window as a painterly motif and spatially familiar everyday device in the introduction. In the ﬁrst chapter, I explore the surface and reﬂection of the medium of glass, the colour gray, the monochrome, as well as the pictorial, in Gerhard Richter’s Eight Gray (2002). The second chapter examines the role of the frame or line in Serge Nitegeka’s Black Lines (2012), as an environment of experience that relies on painted diagrams and the illusion of perspectival space. The third chapter observes a shift in the manner in which Richter and Nitegeka experiment and extend their practices through an engagement with the mirror and the door, respectively, as ways of exploring the threshold. Finally, I discuss my own practice and reﬂect on the exhibition Through the Extent (2015), which was submitted as the practical component of this research.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulﬁlment of the degree of Masters of Arts in Fine Arts (MAFA) Johannesburg, 2017
Keywords: Richter, Gerald--1932-; Nitegeka, Serge--1983-; Art and photography--South Africa|vExhibitions; Painting, Modern--21st century--Exhibitions; Space (Art); Space (Architecture)